Answer:
[tex]{ \rm{S = lw + wh + lh}}[/tex]
• Group the h terms by organised term arrangement :
[tex]{ \rm{S = (wh + lh) + lw}}[/tex]
• Then using distributive property, factorise out the value h so that the reverse is true.
[tex]{ \rm{S = h(w + l) + lw}}[/tex]
• for the variable "lw", divide it by h in order to add it to the bracket of (w + l). Make sure the reverse is true:
[tex]{ \rm{S = h(w + l) + h( \frac{lw}{h} )}} \\ [/tex]
• finally, completely factorise out the value h
[tex] \hookrightarrow \: \: { \boxed{ \boxed { \rm{ \: \: S = h(w + l + \frac{lw}{h} ) \: \: }}}}[/tex]